Peningkatan Pengendalian Manajemen, Kepatuhan Perpajakan, dan Literasi Keuangan untuk Keberlanjutan Bumdes Desa Guntung Besar: Penelitian - Baharuddin, Kurniawan Harminsyah; Khalid Al Hadring Smith; Haris Reza Fathony; Lativa Yuswanita; Titik Wijayati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The management of Village-Owned Enterprises (Bumdes) in Guntung Besar Village faces challenges related to management control and tax compliance, which impact the economic sustainability of the village. Therefore, this community service aims to improve management control and tax compliance in Bumdes through training and socialization on effective management control models and tax obligations such as Corporate Income Tax (PPh Badan) and Value Added Tax (VAT). The implementation of this service was carried out using an interactive training approach, direct mentoring, and simulations. The results show an increase in the understanding of Bumdes managers regarding financial management and tax obligations, which contributes to enhanced transparency and operational accountability. Furthermore, a better understanding of tax obligations encourages Bumdes managers to comply more effectively with applicable tax regulations, thus improving the credibility and sustainability of Bumdes. This community service is expected to serve as a model for other villages in improving the efficient, transparent, and regulation-compliant management of Bumdes.